UNIVERSIDADE E ESCOLA COMO LÓCUS DA PROFISSIONALIZAÇÃO DO ENSINO E DO TEMPO ENTRE-DOIS NO ESTÁGIO SUPERVISIONADO - Vedovatto, Dijnane; de Souza Neto, Samuel [UNESP] (Curriculo sem Fronteiras, 2021)
This work aimed to identify and analyze the professional insertion (IP) of the supervised internship (ES) in Physical Education (EF) and in Graduation (LI) in state schools. In this qualitative research, data from two interlaced surveys are presented, in which the first stage carried out a case study, while the second stage, under development, focused on conducting a collaborative research - intervention. In the first, case study, a mapping of the IP of the ES of EF was made in state schools of what was done; however, in the second, in progress, a collaborative research (intervention) was carried out in the ES of the EF and of the LI of the state schools of the Directorate of Education. 62 people from the educational field participated. In the production of the data it was used: narrative interview, document analysis and content analysis. It was observed in the interns' IP a watershed in the teacher training, involving: tensions, different confrontations, intense learning and challenges when knowing the reality. This process provoked the revision of the ES in the state network from the partnership, concretizing the formation in the time between two.
Keywords: Physical Education; professional development; Teaching Licenses